A method for identifying the boundary of regions in welded coupon specimens using digital image correlation. (15th November 2021) - Yan, Rui; El Bamby, Hagar; Veljkovic, Milan; Xin, Haohui; Yang, Fei
Graphical abstract: Highlights: The slop of minor-major strain relationship reveals the internal transverse constraint in a butt-welded coupon during tensile loading. The HAZ boundary is identified by the slop of the minor-major strain relationship. 'V' and 'monotonic' shapes of the slop distribution along the loading direction exist in the HAZ region. The HAZ boundary identified by the slop of the minor-major strain relationship is verified by hardness and microstructure results. Abstract: The coupon specimen with a transverse butt weld in the middle could be used for determining local constitutive properties of the heat-affected zone (HAZ) and the weld metal (WM) based on the digital image correlation (DIC). However, limited research is reported to demonstrate how to identify the boundary of each region in DIC results. Accordingly, it is difficult to determine the adequate gauge length for measuring the strain of each region and establishing a stress–strain curve for Finite Element Analysis (FEA) of structural problems. In this paper, a method for identifying the region's boundary is proposed based on coupon tests using three steel grades, S355, S500, and S700, corresponding to three weld matching types, match, overmatch, and undermatch, respectively. First, the hardness and the microstructure investigation were conducted to determine the region's boundary. Then, the boundary was identified based on the DIC result using the proposed method. Finally, the identified HAZ regions were verified against hardness results. Using the proposed method, the gauge length for measuring the strain of a single region, such as HAZ and WM, are determined based on the DIC results. The primary purpose is to establish the stress–strain relationship for FEA of welded joints.